School Climate and Teachers’ Perceptions of Parental Involvement in Jewish and Arab Primary Schools in Israel - Schaedel, Bruria; Freund, Anat; Azaiza, Faisal; Hertz-Lazarowitz, Rachel; Boem, Amnon; Eshet, Yovav (International Journal about Parents in Education, 2023)
This study examines educators’ views of parental involvement in the two diverse cultural and national educational systems in Israel. Respondents include 799 teachers from 52 Jewish and Arab primary schools. Our assumption - that Jewish teachers encourage parental involvement more than the Arab teachers, because of the progressive, Western liberal orientation of Jewish schools as opposed to the authoritarian and closed school climate of the Arab schools - was refuted. The findings indicate that in both educational systems, teachers are less inclined to engage in parental involvement. Parents are generally more involved in their children's education at home, while teachers rarely encourage parents' involvement in decision-making processes or voluntary activities in the schools. The teachers' main obstacles with regard to encouraging parental involvement are that they feel disrespected and underappreciated by parents, and they believe they lack the necessary skills to successfully negotiate with parents during crises.